Motivation and retention of health workers in developing countries: a systematic review - Blaauw Duane; Wyness Laura; Thomas Steve; Bidwell Posy; Willis-Shattuck Mischa; Ditlopo Prudence (BMC, 2008)
Abstract Background A key constraint to achieving the MDGs is the absence of a properly trained and motivated workforce. Loss of clinical staff from low and middle-income countries is crippling already fragile health care systems. Health worker retention is critical for health system performance and a key problem is how best to motivate and retain health workers. The authors undertook a systematic review to consolidate existing evidence on the impact of financial and non-financial incentives on motivation and retention. Methods Four literature databases were searched together with Google Scholar and 'Human Resources for Health' on-line journal. Grey literature studies and informational papers were also captured. The inclusion criteria were: 1) article stated clear reasons for implementing specific motivations to improve health worker motivation and/or reduce medical migration, 2) the intervention recommended can be linked to motivation and 3) the study was conducted in a developing country and 4) the study used primary data. Results Twenty articles met the inclusion criteria. They consisted of a mixture of qualitative and quantitative studies. Seven major motivational themes were identified: financial rewards, career development, continuing education, hospital infrastructure, resource availability, hospital management and recognition/appreciation. There was some evidence to suggest that the use of initiatives to improve motivation had been effective in helping retention. There is less clear evidence on the differential response of different cadres. Conclusion While motivational factors are undoubtedly country specific, financial incentives, career development and management issues are core factors. Nevertheless, financial incentives alone are not enough to motivate health workers. It is clear that recognition is highly influential in health worker motivation and that adequate resources and appropriate infrastructure can improve morale significantly.